Short communication: Production, distribution and conservation analysis of Cherax crayfish endemic to Papua and West Papua Provinces, Indonesia - Ferliana Widyasari; Mohammad Sayuti; Randi Bokhy Syuliana Salampessy (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Widyasari F, Sayuti M, Salampessy RBS. 2021. Short communication: Production, distribution and conservation analysis of Cherax crayfish endemic to Papua and West Papua Provinces, Indonesia. Biodiversitas 22: 3271-3276. Freshwater crayfish is a species from the Parastacidae family that is indigenous to Papua and West Papua Indonesia. This study analyzes the amount of production, economic value, distribution, and conservation of freshwater crayfish endemic to Papua and West Papua. The production data were obtained from Stasiun Karantina Ikan or Fish Quarantine Inspection Agency in Papua and West Papua, Indonesia. Data regarding the price of Cherax crayfish were determined based on interviews with freshwater crayfish sellers. Furthermore, the distribution of freshwater crayfish was explained based on a literature review, while the data of its conservation were retrieved from the IUCN Red List of Threatened Species. Cherax crayfish caught from wild populations in West Papua is known higher than in Papua. Increased sales revenue could support the economy of the local community. There have been 25 species of freshwater crayfish identified, nine of which were from West Papua and 16 from Papua. Three species were under Endangered (EN), Least Concern (LC), Vulnerable (VU) status, respectively. Four species were under Data Deficient (DD) status, while the rest were unidentified. Overfishing of Cherax crayfish causes decline Cherax crayfish stock in the wild, future researchers are expected to conduct more specific studies that include relevant stakeholders regarding the conservation of Cherax crayfish that are endemic to Papua and West Papua.